Effectiveness of Myofascial Release Therapy with Shoulder Taping on Subacromial Impingement Syndrome in Collegiate Basket Ball Players -A Quasi experimental Pilot study - Gandhi, V Mohan; Arun, B; Kumar, RK Punitha (Bangladesh Journal of Medical Science, 2016)
Background: Shoulder complex dysfunction can arise when any of its components goes for malfunction. Overhead athletes cause impingement in the shoulder due to subacromial impingement or anterior instability. Myofascial tightness is found to be the common causative mechanism for the shoulder pain, though the literatures were not detailed in considering the myofascial tightness and the management. Aims & Objective: The aim of the study was to find out the effect of myofascial release therapy with shoulder taping on subacromial impingement syndrome in collegiate basketball players. Quasi experimental pilot study with 38 collegiate basketball players who participated in the university tournaments were selected for the study. 19 players in control group were under myofascial therapy whereas 19 players in experimental group underwent shoulder taping and myofascial release therapy. Result: The outcome measures were pain and functional ability. Pain was assessed using numerical pain rating scale, and functional ability was assessed using SPADI. Unrelated t test was done to evaluate the effect of the treatment for pain value between groups is 13.9 with the p value <0.05% and SPADI scale was 13.8 with the p value <0.05%. The result shows that the myofascial release therapy with shoulder taping had more significant improvement than myofascial release therapy only. Conclusion: Study concludes that shoulder taping and myofascial release therapy helps in reducing pain and improvement of functional disability. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.347-351